The Effectiveness of Learning Using Social Media during the Covid 19 Pandemic in Higher Education - Ismail Hanif Batubara; Kholidah Nur; Ali Topan Lubis; Nanang Arianto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study explains the factual about learning using online media during long-distance lectures during the Covid 19 epidemic. Some students are used as a source of information using a qualitative approach method. By using behaviorism and cognitive theory.Online Distance Learning can take advantage of social media with virtual online learning via video conferencing, teleconferences, in groups on social media. Social media is a way out to get rid of boredom or stress from studying at home. These are new conditions for faculty and students, Makathe role of lecturers is very much needed in managing or managing learning starting from planning, organizing, actuating and evaluating in order to increase the effectiveness of the teaching and learning process during the COVID-19 pandemic.